CORPORATE FINANCING BEHAVIOUR OF SHARIAH COMPLIANT E50 SMEs. A PANEL DATA APPROACH OF GMM. - Razali Haron (UNISSULA, 2016)
Motivated by the recent outstanding growth of Islamic Finance in Malaysia, this study aims to investigate the debt financing behaviour of Shariah compliant E50 SMEs in Malaysia covering the existence of target debt, speed of adjustment and factors affecting the adjustment speed to target debt from 2009 to 2013. The Shariah Advisory Council (SAC), has set up certain standard of parameters as guidelines and carried out periodical monitoring in classifying Shariah compliant securities like the prohibition of activities that involve interest (riba), gambling (maisir), uncertainties and speculative trading (gharar). The dynamic model employed and estimated using the Generalized Method of Moment (GMM). Under the dynamic model, the observed debt of a firm should be equal to its optimal debt. However, with the presence of adjustment cost, a firm performs only a partial adjustment to be at the target debt. The model revealed certain determinants significantly influence target debt financing. The positive relationship between tangibility and capital structure yielded in this study enhances Shariah imposition that debt must be asset-backed which means a firm operating under Islamic principles cannot have debt exceeding the tangible assets. This study contributes to the literature and fills the gap by exploring into a relatively new area of debt financing which is the dynamic aspects and also help to enhance the understanding on debt financing behaviour of Shariah compliant SMEs in Malaysia.